Analisis Laporan Pencatatan Cuti di Kantor Wilayah Direktorat Jenderal Perbendaharaan Provinsi Sumatera Utara Medan - Putri Maulani Arsi; Aqwa Naser Daulay (Madani: Jurnal Ilmiah Multidisiplin, 2023)
The Directorate General of Treasury (DJPb) is one of Echelon I under the Ministry of Finance of the Republic of Indonesia which has the task of carrying out budget formulation and implementation, financial management of public service agencies, and government financial accounting and reporting. This agency, which was formed on January 4 2004, has several vertical agencies throughout Indonesia. One of them, the Regional Office of the General of Treasury (Kanwil DJPb) of North Sumatra province which is the focus in writing this report. While the author was carrying out practical work activities (internships) in the general department, several problems occurred, namely in the grouping of employee leave at the regional office of the Directorate General of Treasury. The employee leave data given to the author is still arranged randomly so that the author is given the task of grouping them according to the type of leave. There are several types of leave including sick leave, maternity leave, annual leave, leave for important reasons, and major leave.